Transcriptional Control of Axon Guidance at Midline Structures - Herrera, Eloísa; Escalante, Augusto (Frontiers in Cell and Developmental Biology, 2022)
The development of the nervous system is a time-ordered and multi-stepped process that includes neurogenesis and neuronal specification, axonal navigation, and circuits assembly. During axonal navigation, the growth cone, a dynamic structure located at the tip of the axon, senses environmental signals that guide axons towards their final targets. The expression of a specific repertoire of receptors on the cell surface of the growth cone together with the activation of a set of intracellular transducing molecules, outlines the response of each axon to specific guidance cues. This collection of axon guidance molecules is defined by the transcriptome of the cell which, in turn, depends on transcriptional and epigenetic regulators that modify the structure and DNA accessibility to determine what genes will be expressed to elicit specific axonal behaviors. Studies focused on understanding how axons navigate intermediate targets, such as the floor plate of vertebrates or the mammalian optic chiasm, have largely contributed to our knowledge of how neurons wire together during development. In fact, investigations on axon navigation at these midline structures led to the identification of many of the currently known families of proteins that act as guidance cues and their corresponding receptors. Although the transcription factors and the regulatory mechanisms that control the expression of these molecules are not well understood, important advances have been made in recent years in this regard. Here we provide an updated overview on the current knowledge about the transcriptional control of axon guidance and the selection of trajectories at midline structures.